2014
DOI: 10.1002/anie.201405730
|View full text |Cite
|
Sign up to set email alerts
|

De Novo 3D Structure Determination from Sub‐milligram Protein Samples by Solid‐State 100 kHz MAS NMR Spectroscopy

Abstract: Solid-state NMR spectroscopy is an emerging tool for structural studies of crystalline, membrane-associated, sedimented, and fibrillar proteins. A major limitation for many studies is still the large amount of sample needed for the experiments, typically several isotopically labeled samples of 10-20 mg each. Here we show that a new NMR probe, pushing magic-angle sample rotation to frequencies around 100 kHz, makes it possible to narrow the proton resonance lines sufficiently to provide the necessary sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
288
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(295 citation statements)
references
References 35 publications
2
288
0
5
Order By: Relevance
“…Ap owerful strategy to increase resolution and sensitivity is based on proton-detected experiments applieda th ighM AS frequencies, with deuterated samples that are re-protonated at amide sites. [9][10][11][12][13][14] Fast MAS and deuteration extend the coherence lifetimes T 2 ' of 1 H, 15 Na nd 13 Cn uclei, resulting in two beneficial effects:1 )the associated narrow line widths increase resolution and intensity,and 2) the coherence transfer between nuclei becomes more efficient, which furtheri ncreases sensitivity in correlation experiments.D ifferent 3D experimentsh ave been proposed to correlate the amide site ( 1 H-15 N) to the 13 Ca, 13 Cb and 13 CO nuclei of the same amino acid residue (intra-residue H i -N i -C i )a nd preceding residue (H i -N i -C iÀ1 ). [15][16][17] Sequential assignment of amides is achievedb ym atching the 13 C i and 13 C iÀ1 frequencies of different amide sites.…”
Section: Introductionmentioning
confidence: 99%
“…Ap owerful strategy to increase resolution and sensitivity is based on proton-detected experiments applieda th ighM AS frequencies, with deuterated samples that are re-protonated at amide sites. [9][10][11][12][13][14] Fast MAS and deuteration extend the coherence lifetimes T 2 ' of 1 H, 15 Na nd 13 Cn uclei, resulting in two beneficial effects:1 )the associated narrow line widths increase resolution and intensity,and 2) the coherence transfer between nuclei becomes more efficient, which furtheri ncreases sensitivity in correlation experiments.D ifferent 3D experimentsh ave been proposed to correlate the amide site ( 1 H-15 N) to the 13 Ca, 13 Cb and 13 CO nuclei of the same amino acid residue (intra-residue H i -N i -C i )a nd preceding residue (H i -N i -C iÀ1 ). [15][16][17] Sequential assignment of amides is achievedb ym atching the 13 C i and 13 C iÀ1 frequencies of different amide sites.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, ILV-methyl labeling with suitable precursors has been used for structure determinations (16,28,40), and other tailored labeling approaches have also been proposed (41). However, these methods still introduce only a limited set of side-chain protons.…”
mentioning
confidence: 99%
“…High-resolution proton-detected methods were first demonstrated with modest spinning frequencies by today's standards (∼10 kHz) and relied on a reduction of 1 H-1 H couplings by high levels of dilution with deuterium, typically perdeuteration, and complete (8,9) or partial (10)(11)(12) protonation at exchangeable sites. The need for narrow proton resonances without such extreme levels of deuteration has motivated a continuous technological development, resulting in a dramatic increase in the available spinning frequency (13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[45][46][47][48][49] Because of this reason and due to the enhanced signal-to-noise ratio rendered by proton detection, the development of protonbased solid-state NMR techniques has been the main focus of recent ultrafast-MAS studies. [50][51][52][53][54][55][56][57][58][59][60] Recent studies from our laboratory have demonstrated the feasibility of recoupling proton-proton dipolar couplings, 14,[61][62][63] protonbased multidimensional experiments, [64][65][66][67] spectral-editing techniques, 68,69 and proton-proton distance measurements 69 under ultrafast-MAS conditions, whereas effective use of deuteration has also very recently been shown to be useful in proton-proton distance measurements by Reif et al 70,71 We have also shown the role of dipolar couplings that control the efficiency of refocused-INEPT pulse sequence under ultrafast-MAS. 72 While the recent proton-based ultrafast-MAS studies have successfully demonstrated the feasibility of using wellresolved proton chemical shift resonances, there is a need for methods to assign proton resonances.…”
Section: Introductionmentioning
confidence: 99%